Parties and democracy : party structure and party performance in old and new democracies (Oxford, UK ; Malden, MA : Blackwell, 1998)
This book presents about Party Structure and Party Performance in Old and New Democracies.
Keywords: Politics; Democracy; Political parties; General Agreement on tariffs and trade (1947); Comparative government